CONTEXTUALISING FORM AND FUNCTION FOR THE SAKE OF THE LEARNERS IN CLT - Fudyartanto, Fuad Arif (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
Arguments that the ultimate purpose of L2 acquisition and learning is to communicate have been widely accepted. To get a better result, a combination of instruction and opportunities to practice in communication is necessary. Instruction can provide learners with communicative competence, and practice can improve the automatic processing of this competence to communicate (Brown, 2001). CLT instruction should therefore equip L2 learners with both formal and functional aspects of the language. Depending on the context of the learners, focus on form and function are here viewed as a continuum and complementary to each other. By doing so, it is expected that L2 learners are well provided with ability to perceive not only the whole picture (in this case to communicate) but also small pieces (of grammar, form). It is believed that SLTL with activities that focus on both form (grammar) and function (communication) tends to produce learners with greater accuracy and fluency.